2016
DOI: 10.1530/eje-15-0832
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting pasireotide responsiveness in somatotroph pituitary adenomas resistant to first-generation somatostatin analogues: an immunohistochemical study

Abstract: Aim: To gather data regarding factors predicting responsiveness to pasireotide in acromegaly. Patients and methods: SSTR2a, SSTR3, SSTR5, AIP, Ki-67 and the adenoma subtype were evaluated in somatotroph adenomas from 39 patients treated post-operatively with somatostatin analogues (SSAs). A standardized SSTR scoring system was applied (scores 0-3). All patients received first-generation SSAs, and 11 resistant patients were subsequently treated with pasireotide LAR. Results: None of the patients with negative o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
112
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 46 publications
12
112
2
1
Order By: Relevance
“…Also, tumors with low levels of somatostatin receptor subtype 2 (SSTR2) tend to have a lower responsiveness to treatment with SSTR2-specific SSA like octreotide (Ferone et al 2008, Taboada et al 2008. Responses to pasireotide, a multi-somatostatin receptor specific ligand, also appear to be related to somatostatin receptor subtype 5 (SSTR5) expression (Iacovazzo et al 2016). However, for predicting responses to primary pre-operative SSA therapy, noninvasive characteristics are required, which has driven the recent interest in MRI characteristics at diagnosis, particularly the T2 image intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Also, tumors with low levels of somatostatin receptor subtype 2 (SSTR2) tend to have a lower responsiveness to treatment with SSTR2-specific SSA like octreotide (Ferone et al 2008, Taboada et al 2008. Responses to pasireotide, a multi-somatostatin receptor specific ligand, also appear to be related to somatostatin receptor subtype 5 (SSTR5) expression (Iacovazzo et al 2016). However, for predicting responses to primary pre-operative SSA therapy, noninvasive characteristics are required, which has driven the recent interest in MRI characteristics at diagnosis, particularly the T2 image intensity.…”
Section: Discussionmentioning
confidence: 99%
“…This was also shown in a small in vivo study that found that sst5 expression was a biomarker of response to pasireotide in patients whose disease was not controlled with fg-SRL 97 . Somatostatin receptor type 2 expression was also a biomarker of response to pasireotide.…”
Section: Biomarkers Of Treatment Response In Acromegalymentioning
confidence: 54%
“…Somatostatin receptor type 2 expression was also a biomarker of response to pasireotide. In addition, the same study demonstrated that although AIP expression is a biomarker of response to fg-SRL, it did not seem to be a biomarker of the response to pasireotide 97 .…”
Section: Biomarkers Of Treatment Response In Acromegalymentioning
confidence: 96%
See 1 more Smart Citation
“…Tumors that are dependent on cAMP signaling would logically be responsive to the inhibition of this pathway that is mediated by somatostatin analogs, especially those that target the somatostatin receptor type 2 (SSTR2). Those receptors are highly expressed in most somatotroph tumors, but recent studies have suggested that SSTR2 may be downregulated in the sparsely granulated tumors (Kato et al 2012, Brzana et al 2013, Casar-Borota et al 2013, Mayr et al 2013, Kiseljak-Vassiliades et al 2015b, Iacovazzo et al 2016.…”
Section: :3mentioning
confidence: 99%